Ketoacidosis at diagnosis of type 1 diabetes: Effect of prospective studies with newborn genetic screening and follow up of risk children - Hekkala AM; Ilonen J; Toppari J; Knip M; Veijola R (WILEY, 2022)
We studied the frequency of diabetic ketoacidosis (DKA) in children at diagnosis of type 1 diabetes (T1D) in a region where newborn infants have since 1995 been recruited for genetic screening for human leukocyte antigen (HLA)-conferred disease susceptibility and prospective follow up. The aim was to study whether participation in newborn screening and follow up affected the frequency of DKA, and to follow the time trends in DKA frequency. We first included children born in Oulu University Hospital since 1995 when the prospective studies have been ongoing and diagnosed with T1D <15 years by 2015 (study cohort 1, n = 517). Secondly, we included all children diagnosed with T1D <15 years in this center during 2002-2014 (study cohort 2, n = 579). Children who had an increased genetic risk for T1D and participated in prospective follow up had low frequency of DKA at diagnosis (5.0%). DKA was present in 22.7% of patients not screened for genetic risk, 26.7% of those who were screened but had not an increased risk and 23.4% of children with increased genetic risk but who were not followed up. In study cohort 2 the overall frequency of DKA was 18.5% (13.0% in children <5 years, 14.0% in children 5-10 years and 28.6% in children 10 years at diagnosis; P<.001). In children <2 years the frequency of DKA was 17.1%. Participation in prospective follow-up studies reduces the frequency of DKA in children at diagnosis of T1D, but genetic screening alone does not decrease DKA risk.